Positive electrode active material and preparation method thereof, positive electrode slurry, positive electrode plate, sodium ion battery and application

By using multi-element synergistic effects of Zr, Ti and Zn co-doped in the positive electrode active material of sodium ion batteries, the problem of poor cycle stability of sodium ion batteries is solved, and excellent cycle stability and extended battery life are achieved under high-ratio conditions.

CN119852386AActive Publication Date: 2025-04-18SHENZHEN POWER SUPPLY BUREAU

Patent Information

Application Number
CN202411955162.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The poor circulation stability of sodium ion batteries limits their application.

Method used

The positive electrode active material co-doped by Zr, Ti and Zn is used to suppress phase change through multi-element synergistic effect, increase the layer spacing and broaden the sodium ion diffusion channel, and form a high-entropy structure to improve cyclic stability.

Benefits of technology

The cycle stability of the positive electrode active material is significantly improved, especially under high magnification conditions, which extends the cycle life of the battery and improves thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852386A_ABST
    Figure CN119852386A_ABST
Patent Text Reader

Abstract

The invention relates to a positive active material and a preparation method thereof, positive slurry, a positive pole piece, a sodium ion battery and application, the general formula of the positive active material is NayZraTibZncNidFefMneMxO2, M is one or more of V, Co, Al, Nb, Pb, Sb and Mo, 0.01 < = a < = 0.05, 0.01 < = b < = 0.03, 0.01 < = c < = 0.03, 0 < = x < = 0.05, 0.7 < = y < = 0.85, 0 < = d < = 0.4, 0 < = f < = 0.4, 0 < = e < = 0.4, and a + b + c + d + e + f + x = 1. According to the positive electrode active material, co-doping of Zr, Ti and Zn and a multi-element synergistic effect are utilized, so that phase change is inhibited, the interlayer spacing of the positive electrode active material is increased, a sodium ion diffusion channel is widened, and the positive electrode active material has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode slurry, a positive electrode sheet, a sodium ion battery and applications. Background Art

[0002] Lithium-ion batteries are widely used in all aspects of daily life. However, the scarcity and uneven distribution of lithium resources have forced people to look for alternatives to lithium-ion batteries. Sodium-ion batteries have a similar working principle to lithium-ion batteries and are low-cost and have readily available raw materials. They have received widespread attention in recent years, but sodium-ion batteries currently have the problem of poor cycle stability, which greatly limits their application. Summary of the invention

[0003] Based on this, it is necessary to provide a positive electrode active material and a preparation method thereof, a positive electrode slurry, a positive electrode sheet, a sodium ion battery and applications that can improve cycle stability.

[0004] In one aspect of the present application, a positive electrode active material is provided, wherein the general formula of the positive electrode active material is Na y Zr a Ti b Zn c Ni d Fe f Mn e M x O2, wherein M is one or more of V, Co, Al, Nb, Pb, Sb and Mo, 0.01≤a≤0.05, 0.01≤b≤0.03, 0.01≤c≤0.03, 0≤x≤0.05, 0.7≤y≤0.85, 0≤d≤0.4, 0≤f≤0.4, 0≤e≤0.4, a+b+c+d+e+f+x=1.

[0005] The above-mentioned positive electrode active material is co-doped with Zr, Ti and Zn, and the multi-element synergistic effect suppresses the phase change, so that the crystal structure of the positive electrode active material is not easy to undergo irreversible phase change or collapse during the sodium ion insertion and extraction process, thereby improving the cycle stability of the positive electrode active material; in addition, the above-mentioned multi-element synergistic effect increases the interlayer spacing of the positive electrode active material, broadens the sodium ion diffusion channel, and further improves the cycle stability of the positive electrode active material, especially making the positive electrode active material exhibit excellent cycle stability under high rate conditions. In addition, the above-mentioned multi-element synergistic effect stabilizes the layered structure of the positive electrode active material, avoids changes in interlayer spacing and interlayer slip. In addition, the present application contains a variety of different metal elements in the positive electrode active material, so that these metal elements present a highly disordered distribution in the lattice, forming a high entropy structure, thereby further strengthening the lattice structure and further suppressing the phase change, improving the ion diffusion power, improving the battery capacity, and improving the thermal stability of the positive electrode active material. The above-mentioned positive electrode active material also has the advantages of being non-toxic and easy to prepare.

[0006] In some embodiments, the positive electrode active material satisfies at least one of the following:

[0007] (1) The discharge platform position of the positive electrode active material is 2.5V~3.0V and / or 3.5V~4.0V;

[0008] (2) The platform capacity of the positive electrode active material accounts for less than or equal to 50% of the total capacity;

[0009] (3) The platform capacity of the positive electrode active material at a voltage of 3.5V to 4.0V accounts for a proportion of the total capacity that is less than or equal to 30%.

[0010] In some embodiments, the positive electrode active material is a layered oxide.

[0011] In some embodiments, 0 <d≤0.4,0<f≤0.4,0<e≤0.4。

[0012] In some embodiments, the positive electrode active material comprises a structural formula of Na 0.85 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.33 Mn 0.35 O2、Na 0.82 Ti 0.02 Zn 0.01 Zr 0.02 Ni 0.25 Fe 0.33 Mn 0.35 Sb 0.02O2、Na 0.82 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.2 Fe 0.33 Mn 0.37 Al 0.03 O2, , Na 0.8 Ti 0.03 Zn 0.02 Zr 0.02 Ni 0.23 Fe 0.33 Mn 0.35 Nb 0.02 O2、Na 0.75 Ti 0.01 Zn 0.03 Zr 0.05 Ni 0.25 Fe 0.31 Mn 0.35 O2 and Na 0.75 Ti 0.01 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.32 Mn 0.35 Sb 0.02 At least one of O2.

[0013] In some embodiments, the positive electrode active material includes a sodium layer and a transition metal layer, the interlayer spacing of the sodium layer is 3.15Å~3.30Å; and / or, the interlayer spacing of the transition metal layer is 1.95Å~2.20Å.

[0014] In some embodiments, the lattice parameter a of the positive electrode active material is 2.91 Å ~2.96 Å; and / or, the lattice parameter c is 15.90 Å ~16.20 Å.

[0015] In some embodiments, the median particle size D50 of the positive electrode active material is 5 μm to 10 μm.

[0016] In some embodiments, the specific surface area of ​​the positive electrode active material is 0.4 m 2 / g~0.8m 2 / g.

[0017] In some embodiments, the positive electrode active material satisfies at least one of the following conditions:

[0018] (1) The positive electrode active material is a P2 / O3 mixed phase structure;

[0019] (2) The mass content of the P2 phase in the positive electrode active material is 5% to 30%;

[0020] (3) The mass content of the O3 phase in the positive electrode active material is 70% to 95%.

[0021] In some embodiments, the positive electrode active material satisfies at least one of the following conditions:

[0022] (1) The 2θ with the highest intensity peak in the XRD spectrum is 14°~16°;

[0023] (2) The 2θ of the secondary intensity peak in the XRD spectrum is 40°~45°;

[0024] (3) The half-width of the peak corresponding to the (003) crystal plane in the XRD spectrum is 0.05°~0.5°.

[0025] The second aspect of the present application provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:

[0026] Dissolving a sodium source, an optional iron source, an optional manganese source, an optional nickel source, a titanium source, a zirconium source, a zinc source and an optional metal M source and a complexing agent in a solvent according to the stoichiometric molar ratio of the positive electrode active material, and blending the mixture to obtain a mixed solution;

[0027] The mixed solution is subjected to a heating treatment to obtain a mixed gel;

[0028] The mixed gel is dried to obtain the positive electrode active material.

[0029] In some embodiments, the method for preparing the positive electrode active material satisfies at least one of the following:

[0030] (1) The sodium source includes at least one of sodium dihydrogen carbonate, sodium carbonate, sodium acetate and sodium citrate;

[0031] (2) The iron source includes ferric nitrate;

[0032] (3) the manganese source includes at least one of manganese acetate and manganese nitrate;

[0033] (4) The nickel source includes at least one of nickel nitrate and nickel acetate;

[0034] (5) The titanium source includes at least one of titanium dioxide and titanium nitrate;

[0035] (6) The zirconium source includes at least one of zirconium oxide and zirconium nitrate;

[0036] (7) The zinc source includes at least one of zinc acetate and zinc nitrate;

[0037] (8) The metal M source is at least one of acetate, nitrate and oxide of metal M;

[0038] (9) The complexing agent includes citric acid.

[0039] In some embodiments, the heating temperature of the heating treatment is 60°C to 110°C; and / or the drying temperature of the drying treatment is 80°C to 130°C, and the drying time of the drying treatment is 5h to 15h.

[0040] In some embodiments, a calcination step is further included after the heat treatment, and the calcination includes the following steps:

[0041] The mixed gel after drying was heated to 500°C~600°C at a heating rate of 3°C / min~8°C / min and then calcined for 3 h~7 h;

[0042] The mixed gel after calcination is heated to 850°C to 950°C at a heating rate of 3°C / min to 8°C / min and then kept at this temperature for 10 h to 15 h to obtain the positive electrode active material.

[0043] The third aspect of the present application provides a positive electrode slurry, comprising the positive electrode active material as described in the first aspect and the positive electrode active material prepared by the preparation method as described in the second aspect.

[0044] In some embodiments, the positive electrode slurry includes the positive electrode material, a conductive agent, a binder and a solvent.

[0045] In some embodiments, the positive electrode slurry satisfies at least one of the following conditions:

[0046] (1) The mass ratio of the positive electrode material, the conductive agent and the binder is 0.8-0.9: 0.03-0.2: 0.03-0.2;

[0047] (2) The conductive agent includes at least one of Super P, graphene, carbon dots, CNT and Ketjen black;

[0048] (3) The binder includes at least one of difluoroethylene, polyvinylidene fluoride and tetrafluoroethylene-hexafluoropropylene copolymer;

[0049] (4) The solid content of the positive electrode slurry is 50% to 60%.

[0050] The fourth aspect of the present application provides a conductive coating, the components of which include the positive electrode active material, conductive agent and binder as described in the first aspect; or, the conductive coating is made of the positive electrode slurry as described in the third aspect.

[0051] The fifth aspect of the present application provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active layer, wherein the positive electrode active layer is arranged on at least one side of the positive electrode collector, and the positive electrode active layer comprises the positive electrode active material as described in the first aspect; or the positive electrode active layer is made of the positive electrode slurry as described in the third aspect.

[0052] In some embodiments, the positive electrode sheet satisfies at least one of the following conditions:

[0053] (1) The thickness of the positive electrode plate is 0.2 mm to 0.3 mm;

[0054] (2) The compaction density of the positive electrode sheet is 1.5 g / cm 3 ~3.0g / cm 3 .

[0055] The sixth aspect of the present application provides a sodium ion battery, comprising the positive electrode sheet as described in the fifth aspect.

[0056] The seventh aspect of the present application provides an electrical device comprising the sodium ion battery as described in the sixth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The capacity differential curve of the battery prepared in Example 1 in the 2-4V voltage window.

[0058] Figure 2 The charge and discharge curve of the battery prepared in Example 1 under the 2-4V voltage window 1C.

[0059] Figure 3 The capacity differential curve of the battery prepared in Example 2 in the 2-4.2V voltage window.

[0060] Figure 4 The charge and discharge curves of the battery prepared in Example 2 in the 2-4.2V voltage window.

[0061] Figure 5 This is the 2C cycle curve of the battery prepared in Example 3 in the 2-4V voltage window.

[0062] Figure 6 This is the cycle curve of the battery prepared in Comparative Example 1 in the 2-4V voltage window. DETAILED DESCRIPTION

[0063] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0064] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0065] When a sodium-ion battery is charged, sodium ions are deintercalated from the positive electrode active material, migrate to the negative electrode through the electrolyte, and are embedded in the negative electrode material. At the same time, electrons flow from the positive electrode to the negative electrode through the external circuit to maintain charge balance. When discharging, the opposite is true. Sodium ions are deintercalated from the negative electrode, re-embedded into the positive electrode through the electrolyte, and electrons flow from the negative electrode to the positive electrode through the external circuit, thus forming a current and providing electrical energy to the external circuit. During the cyclic charge and discharge process, the electrode materials of sodium-ion batteries may undergo structural phase changes, particle breakage, pulverization, and other problems, resulting in poor interface stability between the electrode and the electrolyte, affecting the cycle stability.

[0066] Based on this, one embodiment of the present application provides a positive electrode active material, the general formula of the positive electrode active material is Na y Zr a Ti b Zn c Ni d Fe f Mn e M x O2, wherein M is one or more of V, Co, Al, Nb, Pb, Sb and Mo, 0.01≤a≤0.05, 0.01≤b≤0.03, 0.01≤c≤0.03, 0≤x≤0.05, 0.7≤y≤0.85, 0≤d≤0.4, 0≤f≤0.4, 0≤e≤0.4, a+b+c+d+e+f+x=1.

[0067] The above-mentioned positive electrode active material is co-doped with Zr, Ti and Zn, and the multi-element synergistic effect suppresses the phase change, so that the crystal structure of the positive electrode active material is not easy to undergo irreversible phase change or collapse during the sodium ion insertion and extraction process, thereby improving the cycle stability of the positive electrode active material; in addition, the above-mentioned multi-element synergistic effect increases the interlayer spacing of the positive electrode active material, broadens the sodium ion diffusion channel, and further improves the cycle stability of the positive electrode active material, especially making the positive electrode active material exhibit excellent cycle stability under high rate conditions. In addition, the above-mentioned multi-element synergistic effect stabilizes the layered structure of the positive electrode active material, avoids changes in interlayer spacing and interlayer slip. In addition, the present application contains a variety of different metal elements in the positive electrode active material, so that these metal elements present a highly disordered distribution in the lattice, forming a high entropy structure, thereby further strengthening the lattice structure and further suppressing the phase change, improving the ion diffusion power, improving the battery capacity, and improving the thermal stability of the positive electrode active material. The above-mentioned positive electrode active material also has the advantages of being non-toxic and easy to prepare.

[0068] As an example, a can be 0.01, 0.02, 0.03, 0.04 and 0.05, or can be within a range consisting of any two of the above values ​​as end values. Preferably, a is 0.02 to 0.03.

[0069] As an example, b can be 0.01, 0.02 and 0.03, or can be within a range consisting of any two of the above values ​​as end values. Preferably, b is 0.01 to 0.02.

[0070] c can be 0.01, 0.02 and 0.03, or can be in a range consisting of any two of the above values ​​as end values. Preferably, c is 0.02.

[0071] x can be 0, 0.01, 0.02, 0.03, 0.04 and 0.05, or can be in a range consisting of any two of the above values ​​as end values. Preferably, x is 0.02 to 0.04.

[0072] y can be 0.7, 0.75, 0.8, 0.82, 0.83 and 0.85, or can be within a range consisting of any two of the above values ​​as end values. y is preferably 0.75 to 0.83.

[0073] d can be 0, 0.1, 0.2, 0.3, 0.4, or can be in the range consisting of any two of the above values ​​as end values. Preferably, d is 0.2 to 0.33.

[0074] f can be 0, 0.1, 0.2, 0.3, 0.4, or can be in the range of any two of the above values ​​as end values. f is preferably 0.25 to 0.33.

[0075] e can be 0, 0.1, 0.2, 0.3, 0.4, or can be in the range of any two of the above values ​​as end values. e is preferably 0.3 to 0.37.

[0076] M is preferably Nb, Sb and Al.

[0077] In some embodiments, 0 <d≤0.4,0<f≤0.4,0<e≤0.4。

[0078] In some embodiments, the positive electrode active material comprises a structural formula of Na 0.85 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.33 Mn 0.35 O2、Na 0.82 Ti 0.02 Zn 0.01 Zr 0.02 Ni 0.25 Fe 0.33 Mn 0.35 Sb 0.02 O2、Na 0.82 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.2 Fe 0.33 Mn 0.37 Al 0.03 O2, , Na 0.8 Ti 0.03 Zn 0.02 Zr 0.02 Ni 0.23 Fe 0.33 Mn 0.35 Nb 0.02 O2、Na 0.75 Ti 0.01 Zn 0.03 Zr 0.05 Ni 0.25 Fe 0.31 Mn 0.35 O2 and Na 0.75 Ti 0.01 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.32 Mn 0.35 Sb 0.02 At least one of O2.

[0079] In some embodiments, the discharge platform position of the positive electrode active material is 2.5V~3.0V and / or 3.5V~4.0V. The positive electrode active material has few platforms, only one or two platforms, and correspondingly less phase changes, which improves cycle stability.

[0080] In some embodiments, the platform capacity of the positive electrode active material accounts for less than or equal to 50% of the total capacity. A low platform capacity ratio of the positive electrode active material indicates a small phase change and high stability.

[0081] Furthermore, the platform capacity of the positive electrode active material accounts for 20% to 50% of the total capacity.

[0082] Furthermore, the platform capacity of the positive electrode active material accounts for 20% to 40% of the total capacity. The platform capacity accounts for 20% to 40% of the total capacity within this range, which further reduces the phase change and improves the cycle stability of the positive electrode active material.

[0083] In some embodiments, the platform capacity of the positive electrode active material at a voltage of 3.5V to 4.0V accounts for less than or equal to 30% of the total capacity.

[0084] Furthermore, the platform capacity of the positive electrode active material accounts for 20% to 30% of the total capacity at a voltage of 3.5V to 4.0V.

[0085] In some embodiments, the platform capacity of the positive electrode active material accounts for less than or equal to 50% of the total capacity, and the platform capacity of the positive electrode active material accounts for less than or equal to 30% of the total capacity at a voltage of 3.5V to 4.0V. The platform capacity of the positive electrode active material has a low proportion, and the platform capacity has a low proportion under high pressure, which reduces phase change and improves cycle stability.

[0086] In some embodiments, the discharge platform position of the positive electrode active material is 2.5V~3.0V and 3.5V~4.0V, the platform capacity of the positive electrode active material accounts for less than or equal to 50% of the total capacity, and the platform capacity at a voltage of 3.5V~4.0V accounts for less than or equal to 30% of the total capacity. The positive electrode active material has few charge and discharge platforms, a low platform capacity ratio, and very few phase changes, thereby improving cycle stability.

[0087] In some embodiments, the positive electrode active material is a layered oxide.

[0088] The positive electrode active material is co-doped with Zr, Ti and Zn to form a high-entropy sodium ion layered oxide. The synergistic effect of multiple elements inhibits phase change, making it difficult for the crystal structure of the high-entropy sodium ion layered oxide to undergo irreversible phase change or collapse during the sodium ion insertion and extraction process, thereby improving the cycle stability of the positive electrode active material. In addition, the synergistic effect of the multiple elements increases the interlayer spacing of the high-entropy sodium ion layered oxide, broadens the sodium ion diffusion channel, and further improves the cycle stability of the positive electrode active material, so that the positive electrode active material exhibits excellent cycle stability under high rate conditions.

[0089] In some embodiments, the positive electrode active material includes a sodium layer and a transition metal layer, and the interlayer spacing of the sodium layer is 3.15Å~3.30Å.

[0090] As an example, the interlayer spacing of the sodium layer can be 3.15 Å, 3.16 Å, 3.17 Å, 3.18 Å, 3.19 Å, 3.20 Å, 3.21 Å, 3.22 Å, 3.23 Å, 3.24 Å, 3.25 Å, 3.26 Å, 3.27 Å, 3.28 Å, 3.29 Å and 3.30 Å, or it can be in the range consisting of any two of the above point values ​​as end values. The interlayer spacing of the sodium layer is preferably 3.18 to 3.28 Å.

[0091] It is understood that the layered structure of the positive electrode active material is composed of transition metal layers and sodium layers arranged crosswise along the c-axis direction; the transition metal layers are formed by interconnected MO6 octahedral units through edge sharing, and the sodium ions are located between the transition metal layers.

[0092] In some embodiments, the positive electrode active material includes a sodium layer and a transition metal layer, and the interlayer spacing of the transition metal layer is 1.95Å~2.20Å.

[0093] As an example, the interlayer spacing of the transition metal layer can be 1.95 Å, 1.96 Å, 1.97 Å, 1.98 Å, 1.99 Å, 2.00 Å, 2.01 Å, 2.02 Å, 2.03 Å, 2.04 Å, 2.05 Å, 2.06 Å, 2.07 Å, 2.08 Å, 2.09 Å, 2.10 Å, 2.11 Å, 2.12 Å, 2.13 Å, 2.14 Å, 2.15 Å, 2.16 Å, 2.17 Å, 2.18 Å, 2.19 Å and 2.20 Å, or it can be in the range consisting of any two of the above point values ​​as end values. The interlayer spacing of the transition metal layer is preferably 2.10 Å ~ 2.2 Å.

[0094] In some embodiments, the positive electrode active material includes a sodium layer and a transition metal layer, and the interlayer spacing of the sodium layer is 3.15Å~3.30Å; and / or, the interlayer spacing of the transition metal layer is 1.95Å~2.20Å. Under this interlayer spacing, the positive electrode active material can not only maintain structural stability, but also is not prone to irreversible phase change, and is also conducive to the diffusion of sodium ions, further improving the cycle stability of the positive electrode active material under high rate conditions and extending the cycle life.

[0095] In some embodiments, an XRD test is performed on the positive electrode active material, and the data is refined using GSAS software to obtain the interlayer spacing of the sodium layer and the interlayer spacing of the transition metal layer.

[0096] In some embodiments, the lattice parameter a of the positive electrode active material is 2.91 Å to 2.96 Å. In some embodiments, the lattice parameter c of the positive electrode active material is 15.90 Å to 16.20 Å.

[0097] In some embodiments, the lattice parameter a of the positive electrode active material is 2.91 Å to 2.96 Å, and the lattice parameter c of the positive electrode active material is 15.90 Å to 16.20 Å. The positive electrode active material having this unit cell side length feature is more conducive to sodium ion diffusion, thereby further improving the capacity, cycle stability and rate performance of the battery.

[0098] In some embodiments, the median particle size D50 of the positive electrode active material is 5 μm to 15 μm.

[0099] As an example, the median particle size of the positive electrode active material can be 5μm, 5.5μm, 5.9μm, 6μm, 6.3μm, 6.5μm, 7μm, 7.2μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 9.6μm, 10μm, 11μm, 12μm, 13μm, 14μm and 15μm, or it can be within the range formed by any two of the above point values ​​as end values.

[0100] Furthermore, the median particle size D50 of the positive electrode active material is 5 μm to 10 μm. At this median particle size, the diffusion path of sodium ions in the active material can be shortened, the diffusion speed can be accelerated, and the battery charging and discharging efficiency can be higher; and at this median particle size, the volume change of the positive electrode active material during the charging and discharging process is relatively uniform, which can reduce particle breakage, pulverization and structural damage caused by volume expansion and contraction, thereby further improving the cycle stability and extending the service life.

[0101] Furthermore, the median particle size of the positive electrode active material is 5 μm to 8.0 μm. The battery 300 cycle capacity retention rate is higher at this median particle size.

[0102] In some embodiments, the specific surface area of ​​the positive electrode active material is 0.2 m 2 / g~0.8m 2 / g.

[0103] As an example, the specific surface area of ​​the positive electrode active material may be 0.2 m 2 / g, 0.3 m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g,0.7m 2 / g and 0.8m 2 / g, and may be within the range consisting of any two of the above-mentioned point values ​​as end values.

[0104] The specific surface area of ​​the positive electrode active material is preferably 0.4 m 2 / g~0.8m 2 / g.

[0105] At this specific surface area, the number of active sites on the surface of the positive electrode active material increases, and the ion exchange interface between the electrode and the electrolyte increases, making the transmission of sodium ions easier and faster, thereby further improving the charge and discharge efficiency and rate performance of the battery; and at this specific surface area, the utilization rate of the positive electrode active material can be improved, the capacity of the battery can be increased, and the cycle stability can be further improved.

[0106] The specific surface area of ​​the positive electrode active material is more preferably 0.5 m 2 / g~0.6m 2 / g. Under this specific surface area, the battery's 300-cycle capacity retention rate is higher.

[0107] In some embodiments, the positive electrode active material exhibits a plate-like polycrystalline morphology.

[0108] In some embodiments, the positive electrode active material has a P2 / O3 mixed phase structure. The P2 / O3 mixed phase structure retains the interlayer channels of the P2 phase that are conducive to the diffusion of sodium ions, and has the structural stability of the O3 phase, so that the material can better balance the diffusion of lithium ions and the stability of the structure during the charge and discharge process.

[0109] In some embodiments, the mass content of the P2 phase in the positive electrode active material is 5% to 30%. The mass content of the P2 phase in the positive electrode active material is preferably 10% to 25%.

[0110] In some embodiments, the mass content of the O3 phase in the positive electrode active material is 70% to 95%. The mass content of the O3 phase in the positive electrode active material is preferably 75% to 90%.

[0111] In some embodiments, the mass content of the P2 phase in the positive electrode active material is 5% to 30%, and the mass content of the O3 phase in the positive electrode active material is 70% to 95%. The structure of the positive electrode active material with the P2 phase and the O3 phase at this mass content ratio well balances the diffusivity of sodium ions and the stability of the structure, further improving the cycle stability of the positive electrode active material.

[0112] In some embodiments, the positive electrode active material has a 2θ angle of 14° to 16° at the highest peak in the XRD spectrum.

[0113] In some embodiments, for the positive electrode active material, the 2θ of the secondary intensity peak in the XRD spectrum is 40°~45°.

[0114] In some embodiments, the positive electrode active material has a peak half-peak width corresponding to the (003) crystal plane in the XRD spectrum of 0.05°~0.5°.

[0115] The second aspect of the present application provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:

[0116] Dissolving a sodium source, an optional iron source, an optional manganese source, an optional nickel source, a titanium source, a zirconium source, a zinc source and an optional metal M source and a complexing agent in a solvent according to the stoichiometric molar ratio of the positive electrode active material, and blending the mixture to obtain a mixed solution;

[0117] The mixed solution is subjected to a heating treatment to obtain a mixed gel;

[0118] The mixed gel is dried to obtain the positive electrode active material.

[0119] It is understandable that the "optional" in the optional iron source, the optional manganese source, the optional nickel source, and the optional metal M source means that they may or may not be added. y Zr a Ti b Zn c Ni d Fe f Mn e M x When the corresponding subscript in O2 is 0, it is not added.

[0120] The above preparation method adopts a mixing method of sol first and then gel, so that the raw materials are fully mixed, and then the metals are distributed more evenly and orderly in chaos, forming a high entropy material, making it less likely for the positive electrode active material to phase separate or form intermetallic compounds, thereby improving the capacitance and cycle stability of the positive electrode active material.

[0121] In some embodiments, the sodium source includes at least one of sodium dihydrogen carbonate, sodium carbonate, sodium acetate and sodium citrate.

[0122] In some embodiments, the iron source includes ferric nitrate.

[0123] In some embodiments, the manganese source includes at least one of manganese acetate and manganese nitrate.

[0124] In some embodiments, the nickel source includes at least one of nickel nitrate and nickel acetate.

[0125] In some embodiments, the titanium source includes at least one of titanium dioxide and titanium nitrate.

[0126] In some embodiments, the zirconium source includes at least one of zirconium oxide and zirconium nitrate.

[0127] In some embodiments, the zinc source includes at least one of zinc acetate and zinc nitrate.

[0128] In some embodiments, the metal M source is at least one of an acetate, a nitrate and an oxide containing metal M.

[0129] In some embodiments, the complexing agent includes citric acid.

[0130] In some embodiments, the heating temperature of the heat treatment is 60° C. to 110° C. The heating temperature of the heat treatment is preferably 80° C. to 100° C.

[0131] In some embodiments, the drying temperature of the drying treatment is 80°C to 130°C, and the drying time of the drying treatment is 5h to 15h. The drying temperature of the drying treatment is preferably 90°C to 120°C. The drying time of the drying treatment is preferably 10h to 12h.

[0132] In some embodiments, a calcination step is further included after the heat treatment, and the calcination includes the following steps:

[0133] The mixed gel after drying was heated to 500°C~600°C at a heating rate of 3°C / min~8°C / min and then calcined for 3 h~7 h;

[0134] The mixed gel after calcination is heated to 850°C to 950°C at a heating rate of 3°C / min to 8°C / min and then kept at this temperature for 10 h to 15 h to obtain the positive electrode active material.

[0135] In some embodiments, the drying temperature of the drying treatment is 90°C to 120°C, the drying time is 10h to 12h, then the mixed gel after the drying treatment is heated to 500°C to 600°C at a heating rate of 3°C / min to 8°C / min, and then calcined for 3h to 7h, and then the mixed gel after the calcination treatment is heated to 900°C to 950°C at a heating rate of 3°C / min to 8°C / min and kept warm for 10h to 15h to obtain the positive electrode active material. The positive electrode active material prepared under this temperature condition has a more stable structure, better electrochemical performance, and a higher capacity retention rate of the corresponding battery.

[0136] In some embodiments, according to Na y Zr a Ti b Zn c Ni d Fe f Mn e M x O2 in a stoichiometric ratio, add sodium source, iron source, manganese source, nickel source, titanium source, zirconium source, zinc source and metal M source, and add a chelating agent, dissolve in the solvent, stir at room temperature for 0.5h to fully mix, transfer to an oil bath for stirring and heating, evaporate the solvent to obtain a mixed gel, transfer the mixed gel to an oven to dry overnight, grind it and transfer it to a muffle furnace for calcination.

[0137] The third aspect of the present application provides a positive electrode slurry, comprising the positive electrode active material as described in the first aspect and the positive electrode active material prepared by the preparation method as described in the second aspect.

[0138] In some embodiments, the positive electrode slurry includes the positive electrode active material, a conductive agent, a binder, and a solvent.

[0139] Furthermore, the solvent may be NMP (N-methyl-2-pyrrolidone).

[0140] In some embodiments, the mass ratio of the positive electrode material, the conductive agent and the binder is 0.8~0.9: 0.03~0.2: 0.03~0.2.

[0141] In some embodiments, the solid content of the positive electrode slurry is 50% to 60%.

[0142] In some embodiments, the conductive agent includes at least one of Super P, graphene, carbon dots, CNT and Ketjen black. Super P is small particle conductive carbon black; CNT is carbon nanotube.

[0143] In some embodiments, the binder includes at least one of difluoroethylene, polyvinylidene fluoride and tetrafluoroethylene-hexafluoropropylene copolymer.

[0144] In some embodiments, the positive electrode slurry is prepared by uniformly mixing the positive electrode active material, the conductive agent and the binder in a solvent.

[0145] The fourth aspect of the present application provides a conductive coating, the components of which include the positive electrode active material, conductive agent and binder as described in the first aspect; or, the conductive coating is made of the positive electrode slurry as described in the third aspect.

[0146] The fifth aspect of the present application provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active layer, wherein the positive electrode active layer is arranged on at least one side of the positive electrode collector, and the positive electrode active layer comprises the positive electrode active material as described in the first aspect; or the positive electrode active layer is made of the positive electrode slurry as described in the third aspect.

[0147] In some of the embodiments, the positive electrode sheet is prepared by uniformly coating the positive electrode slurry on at least one side of the positive electrode current collector, and drying the positive electrode slurry to form a positive electrode active layer to prepare the positive electrode sheet.

[0148] In some embodiments, the mass percentage of the positive electrode material in the positive electrode active layer is 80% to 90%.

[0149] In some embodiments, the mass percentage of the conductive agent in the positive electrode active layer is 3% to 20%.

[0150] In some embodiments, the mass percentage of the binder in the positive electrode active layer is 3% to 20%.

[0151] Furthermore, the drying temperature is 80° C. to 130° C., and the drying time is 5 h to 13 h.

[0152] Furthermore, the positive electrode current collector is made of aluminum foil.

[0153] Furthermore, the drying equipment adopts an oven.

[0154] In some embodiments, the single-surface density of the positive electrode active layer is 2 mg / cm 2 ~8mg / cm 2 .

[0155] In some embodiments, the thickness of the positive electrode sheet is 0.2 mm to 0.3 mm. The thickness of the positive electrode sheet is the overall thickness of the positive electrode sheet including the positive electrode active layer and the positive electrode current collector.

[0156] In some embodiments, the compaction density of the positive electrode sheet is 1.5 g / cm 3 ~3.0g / cm 3 .

[0157] The fifth aspect of the present application provides a sodium ion battery, comprising the positive electrode sheet as described in the fourth aspect.

[0158] The sodium ion battery also includes a negative electrode plate, which is arranged opposite to the positive electrode plate.

[0159] Furthermore, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector.

[0160] The negative electrode current collector may be copper foil.

[0161] The negative electrode active layer includes a negative electrode active material, a binder and a conductive agent.

[0162] Furthermore, in the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%.

[0163] Furthermore, in the negative electrode active layer, the mass percentage of the binder is 0.1% to 6%.

[0164] Furthermore, in the negative electrode active layer, the mass percentage of the conductive agent is 1% to 8%.

[0165] In some embodiments, the negative electrode active material may be at least one of hard carbon, soft carbon, sodium titanate and antimony trisulfide.

[0166] In some embodiments, the binder in the negative electrode active layer may be at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid and polyamide.

[0167] In some embodiments, the conductive agent in the negative electrode active layer may be at least one of conductive carbon black, Ketjen black, acetylene black and graphene.

[0168] In some embodiments, the sodium ion battery further includes an electrolyte comprising an electrolyte salt and a solvent.

[0169] As an example, 1M NaClO4 EC:DEC=1:1 is used, that is, the concentration of the electrolyte salt in the mixed solvent of EC and DEC is 1M, and the volume ratio of EC and DEC is 1:1.

[0170] The sixth aspect of the present application provides an electrical device comprising the sodium ion battery as described in the fifth aspect.

[0171] Electrical devices include but are not limited to watches, wireless headphones, digital products, smart cards, remote controls, auto parts and electronic products.

[0172] The following are specific embodiments.

[0173] Example 1

[0174] This embodiment provides a positive electrode active material, the positive electrode active material has a structural formula of Na 0.85 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.33 Mn 0.35 O2.

[0175] The preparation method of the positive electrode active material of this embodiment is as follows: sodium acetate is used as a sodium source, titanium dioxide is used as a titanium source, zinc acetate is used as a zinc source, zirconium nitrate is used as a zirconium source, nickel acetate and manganese acetate are used as nickel sources and manganese sources respectively, and ferric nitrate is used as an iron source, and added into deionized water according to a stoichiometric ratio, citric acid is used as a complexing agent, heated in a water bath at 80°C until the deionized water is completely evaporated, transferred to a 120°C oven for drying for 12h, and then transferred to a muffle furnace after grinding, sintered at 500°C for 5h, sintered at 930°C for 12h, and the heating rate is 5°C / min, and Na 0.85 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.33 Mn 0.35 O2 black powder.

[0176] The preparation method of the positive electrode sheet of this embodiment is as follows: the positive electrode active material, the conductive agent Super P, and the binder PVDF are weighed in a mass ratio of 8:1:1, wherein the PVDF is prepared in advance into a PVDF NMP solution with a mass fraction of 4%, the positive electrode active material, Super P and PVDF are mixed to prepare a positive electrode slurry, a small amount of NMP is added to make the solid content of the positive electrode slurry 55%, and the positive electrode slurry is evenly coated on an aluminum foil with a surface density of 3.0 mg / cm 2 , after drying and cold pressing, the positive electrode sheet is obtained.

[0177] Example 2

[0178] This embodiment provides a positive electrode active material, the positive electrode active material has a structural formula of Na 0.8 Ti 0.03 Zn 0.02 Zr 0.02 Ni 0.23 Fe 0.33 Mn 0.35Nb 0.02 O2.

[0179] The positive electrode active material preparation method of the embodiment is as follows: sodium acetate is used as a sodium source, titanium dioxide is used as a titanium source, zinc acetate is used as a zinc source, zirconium nitrate is used as a zirconium source, nickel acetate and manganese acetate are used as nickel sources and manganese sources, respectively, iron nitrate is used as an iron source, and niobium pentoxide is used as a niobium source, and added to deionized water according to a stoichiometric ratio, citric acid is used as a complexing agent, and heated in an oil bath at 100°C until the deionized water is completely evaporated, and then transferred to a 90°C oven for drying for 12 hours, and then transferred to a muffle furnace after grinding, sintered at 600°C for 3 hours, sintered at 950°C for 10 hours, and the heating rate is 5°C / min, and calcined to obtain Na 0.8 Ti 0.03 Zn 0.02 Zr 0.02 Ni 0.23 Fe 0.33 Mn 0.35 Nb 0.02 O2 black powder.

[0180] The preparation method of the positive electrode sheet of this embodiment is as follows: the positive electrode active material, the conductive agent acetylene black, and the binder PVDF are weighed in a mass ratio of 9:0.5:0.5, wherein the PVDF is prepared in advance into a PVDF NMP solution with a mass fraction of 4%, the positive electrode active material, acetylene black and PVDF are mixed to prepare a positive electrode slurry, a small amount of NMP is added to make the solid content of the positive electrode slurry 55%, and the positive electrode slurry is evenly coated on an aluminum foil with a surface density of 3.0 mg / cm 2 , after drying and cold pressing, the positive electrode sheet is obtained.

[0181] Example 3

[0182] This embodiment provides a positive electrode active material, the structural formula of which is Na 0.75 Ti 0.01 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.32 Mn 0.35 Sb 0.02 O2.

[0183] The positive electrode active material preparation method of the embodiment is as follows: sodium acetate is used as a sodium source, titanium nitrate is used as a titanium source, zinc acetate is used as a zinc source, zirconium nitrate is used as a zirconium source, nickel nitrate and manganese nitrate are used as nickel sources and manganese sources, respectively, iron nitrate is used as an iron source, and antimony trioxide is used as an antimony source. They are added into deionized water according to a stoichiometric ratio, citric acid is used as a complexing agent, and the mixture is heated in an oil bath at 100°C until the deionized water is completely evaporated, and then the mixture is transferred to a 100°C oven and dried for 10 hours. After grinding, the mixture is transferred to a muffle furnace, sintered at 500°C for 5 hours, sintered at 900°C for 15 hours, and the heating rate is 5°C / min. After calcination, Na 0.75 Ti 0.01 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.32 Mn 0.35 Sb 0.02 O2 black powder.

[0184] The preparation method of the positive electrode sheet of this embodiment is as follows: the positive electrode active material, the conductive agent Super P, and the binder PVDF are weighed in a mass ratio of 0.85:0.15:0.05, wherein PVDF is prepared in advance into a PVDF NMP solution with a mass fraction of 4%, the positive electrode active material, Super P and PVDF are mixed to prepare a positive electrode slurry, a small amount of NMP is added to make the solid content of the positive electrode slurry 55%, and the positive electrode slurry is evenly coated on an aluminum foil with a surface density of 3.0 mg / cm 2 , after drying and cold pressing, the positive electrode sheet is obtained.

[0185] Example 4

[0186] Example 4 is basically the same as Example 1, except that the median particle size D50 of the positive electrode material is 15 μm. The same proportion and sintering method as Example 1 are used, and a precursor with a particle size D50 of more than 12 μm is used.

[0187] Example 5

[0188] Example 5 is basically the same as Example 1, except that the specific surface area of ​​the positive electrode material is 0.25 m 2 / g, increase the sintering temperature to 1000℃, and extend the sintering time to 20h to make the material grains larger and reduce the specific surface area.

[0189] Comparative Example 1

[0190] Comparative Example 1 provides a positive electrode active material, the structural formula of which is NaNi 0.5 Mn 0.5 O2.

[0191] Comparative Example 1 The preparation method of the positive electrode active material is as follows: sodium acetate is used as a sodium source, nickel nitrate and manganese nitrate are used as a nickel source and a manganese source, respectively, and added to deionized water according to a stoichiometric ratio, citric acid is used as a complexing agent, and heated in an oil bath at 100°C until the deionized water is completely evaporated, and then transferred to a 100°C oven for drying for 10 hours, and then transferred to a muffle furnace after grinding, sintered at 500°C for 5 hours, sintered at 900°C for 15 hours, and the heating rate was 5°C / min, and NaNi was obtained after calcination. 0.5 Mn 0.5 O2 black powder.

[0192] The preparation method of the positive electrode sheet of Comparative Example 1 is as follows: the positive electrode active material, the conductive agent Super P, and the binder PVDF prepared in Comparative Example 1 are weighed in a mass ratio of 8:1:1, wherein the PVDF is prepared in advance into a PVDF NMP solution with a mass fraction of 4%, the positive electrode active material, Super P and PVDF are mixed to prepare a positive electrode slurry, a small amount of NMP is added to make the solid content of the positive electrode slurry 55%, and the positive electrode slurry is evenly coated on an aluminum foil with a surface density of 3.0 mg / cm 2 , after drying and cold pressing, the positive electrode sheet is obtained.

[0193] Comparative Example 2

[0194] Comparative Example 2 is substantially the same as Example 1, except that the zirconium source is omitted during the preparation of the positive electrode active material.

[0195] Comparative Example 3

[0196] Comparative Example 3 is substantially the same as Example 1, except that the titanium source is omitted during the preparation of the positive electrode active material.

[0197] Comparative Example 4

[0198] Comparative Example 4 is substantially the same as Example 1, except that the zinc source is omitted during the preparation of the positive electrode active material.

[0199] The positive electrode active materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested for physical and chemical properties and electrical properties, and the test results are shown in Table 1. The positive electrode sheets prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were assembled with a metal sodium negative electrode to form a 2032 button half-cell. The assembled button cells were placed for 12 hours and then transferred to a LAND tester for performance testing. Charge and discharge cycle tests were performed at voltage windows of 2 to 4 V and 2 to 4.2 V. The second cycle charge and discharge curve was used to make a capacity differential curve or transferred to an electrochemical workstation after one cycle of activation for CV (capacitance-voltage) testing. The test results are shown in Table 2.

[0200] Among them, the test conditions or test standards for each performance test item are:

[0201] Specific surface area: The specific surface area is calculated by measuring the adsorption amount under different relative pressures using the BET equation. The BET method usually uses nitrogen as the adsorbate, performs physical adsorption at liquid nitrogen temperature, and calculates the specific surface area by measuring the adsorption isotherm.

[0202] 0.2C specific capacity:

[0203] a. Let stand for 2 minutes;

[0204] b. Constant current discharge: current 0.2C (calculated according to theoretical capacity), discharge to limit voltage;

[0205] c. Let stand for 10 minutes;

[0206] d. Constant current and constant voltage charging: current 0.2C, charging to cut-off voltage, cut-off current 0.05C;

[0207] e. Let stand for 10 minutes;

[0208] f. Constant current discharge: current 0.2C, discharge to limit voltage;

[0209] gc~f cycle 3 times;

[0210] h. Take the average value of the discharge capacity in step f three times as the battery capacity.

[0211] 2C specific capacity:

[0212] a. Let stand for 2 minutes;

[0213] b. Constant current discharge: current 0.2C (calculated according to theoretical capacity), discharge to limit voltage;

[0214] c. Let stand for 10 minutes;

[0215] d. Constant current and constant voltage charging: current 2C, charging to cut-off voltage, cut-off current 0.05C;

[0216] e. Let stand for 10 minutes;

[0217] f. Constant current discharge: current 2C, discharge to limit voltage;

[0218] gc~f cycle 3 times;

[0219] h. Take the average value of the discharge capacity in step f three times as the battery capacity.

[0220] Table 1

[0221]

[0222] Table 2

[0223]

[0224] It can be seen from Table 1 and Table 2 above that the positive electrode active materials of Examples 1 to 5 utilize the synergistic effect of multiple elements to inhibit phase change, and multiple metal elements form a high entropy structure in the lattice, further strengthening the lattice structure and further inhibiting the phase change, so that the 300-cycle capacity retention rate can be as high as 99.8%, thereby improving the cycle stability. However, it can be seen from Comparative Examples 1 to 4 that the lack of any of the metal elements among Zr, Ti and Zn cannot achieve the technical effect of the present application.

[0225] The capacity differential curve of the battery prepared in Example 1 in the 2-4V voltage window is as follows: Figure 1 As shown, the platform capacity voltage range is 2.6 V~2.9 V, and the discharge platform position is 2.82 V; the charge and discharge curve of the battery prepared in Example 1 under the 2-4 V voltage window 1C is as shown Figure 2 As shown; the capacity differential curve of the battery prepared in Example 2 in the 2-4.2V voltage window is as follows Figure 3 As shown, the platform capacity voltage range is 3.5 V ~ 4.0 V, and the discharge platform position is 3.68 V; the charge and discharge curve of the battery prepared in Example 2 in the 2-4.2 V voltage window is as shown Figure 4 As shown, the discharge capacity in the voltage range of 3.5 V ~ 4.0 V is about 40 mAh / g; the battery prepared in Example 3 has a 2C cycle curve in the 2-4 V voltage window as shown Figure 5 As shown; the cycle curve of the battery prepared in Comparative Example 1 in the 2-4V voltage window is as follows Figure 6 As shown. Figure 5 and Figure 6 It can be seen that the cycle stability of the battery made with the positive electrode active material of the present application is significantly improved.

[0226] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0227] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A positive electrode active material, characterized in that: The general formula of the positive electrode active material is Na y Zr a Ti b Zn c Ni d Fe f Mn e M x O2, wherein M is one or more of V, Co, Al, Nb, Pb, Sb and Mo, 0.01≤a≤0.05, 0.01≤b≤0.03, 0.01≤c≤0.03, 0≤x≤0.05, 0.7≤y≤0.85, 0≤d≤0.4, 0≤f≤0.4, 0≤e≤0.4, a+b+c+d+e+f+x=1.

2. The positive electrode active material according to claim 1, characterized in that At least one of the following is met: (1) The discharge platform position of the positive electrode active material is 2.5V~3.0V and / or 3.5V~4.0V; (2) The platform capacity of the positive electrode active material accounts for less than or equal to 50% of the total capacity; (3) The platform capacity of the positive electrode active material at a voltage of 3.5V to 4.0V accounts for a proportion of the total capacity that is less than or equal to 30%.

3. The positive electrode active material according to claim 1, characterized in that The positive electrode active material is a layered oxide.

4. The positive electrode active material according to claim 1, characterized in that 0 <d≤0.4,0<f≤0.4,0<e≤0.4。 5. The positive electrode active material according to claim 1, characterized in that The structural formula of the positive electrode active material includes Na 0.85 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.33 Mn 0.35 O2、Na 0.82 Ti 0.02 Zn 0.01 Zr 0.02 Ni 0.25 Fe 0.33 Mn 0.35 Sb 0.02 O2、Na 0.82 Ti 0.02 Zn 0.02 Zr 0.03 Ni 0.2 Fe 0.33 Mn 0.37 Al 0.03 O2, , Na 0.8 Ti 0.03 Zn 0.02 Zr 0.02 Ni 0.23 Fe 0.33 Mn 0.35 Nb 0.0 2O2, Na 0.75 Ti 0.01 Zn 0.03 Zr 0.05 Ni 0.25 Fe 0.31 Mn 0.35 O2 and Na 0.75 Ti 0.01 Zn 0.02 Zr 0.03 Ni 0.25 Fe 0.32 Mn 0.35 Sb 0.0 At least one of 2O2.

6. The positive electrode active material according to claim 1, characterized in that The positive electrode active material comprises a sodium layer and a transition metal layer, wherein the interlayer spacing of the sodium layer is 3.15Å~3.30Å; and / or, the interlayer spacing of the transition metal layer is 1.95Å~2.20Å.

7. The positive electrode active material according to any one of claims 1 to 6, characterized in that The lattice parameter a of the positive electrode active material is 2.91 Å ~2.96 Å; and / or, the lattice parameter c of the positive electrode active material is 15.90 Å ~16.20 Å.

8. The positive electrode active material according to any one of claims 1 to 6, characterized in that The median particle size D50 of the positive electrode active material is 5 μm to 10 μm.

9. The positive electrode active material according to any one of claims 1 to 6, characterized in that The specific surface area of ​​the positive electrode active material is 0.4 m 2 / g~0.8m 2 / g.

10. The positive electrode active material according to any one of claims 1 to 6, characterized in that The positive electrode active material satisfies at least one of the following conditions: (1) The positive electrode active material is a P2 / O3 mixed phase structure; (2) The mass content of the P2 phase in the positive electrode active material is 5% to 30%; (3) The mass content of the O3 phase in the positive electrode active material is 70% to 95%.

11. The positive electrode active material according to any one of claims 1 to 6, characterized in that The positive electrode active material satisfies at least one of the following conditions: (1) The 2θ with the highest intensity peak in the XRD spectrum is 14°~16°; (2) The 2θ of the secondary intensity peak in the XRD spectrum is 40°~45°; (3) The half-width of the peak corresponding to the (003) crystal plane in the XRD spectrum is 0.05°~0.5°.

12. A method for preparing a positive electrode active material according to any one of claims 1 to 11, characterized in that: The following steps are involved: Dissolving a sodium source, an optional iron source, an optional manganese source, an optional nickel source, a titanium source, a zirconium source, a zinc source and an optional metal M source and a complexing agent in a solvent according to the stoichiometric molar ratio of the positive electrode active material, and blending the mixture to obtain a mixed solution; The mixed solution is subjected to a heating treatment to obtain a mixed gel; The mixed gel is dried to obtain the positive electrode active material.

13. The method for preparing a positive electrode active material according to claim 12, characterized in that: At least one of the following is met: (1) The sodium source includes at least one of sodium dihydrogen carbonate, sodium carbonate, sodium acetate and sodium citrate; (2) The iron source includes ferric nitrate; (3) the manganese source includes at least one of manganese acetate and manganese nitrate; (4) The nickel source includes at least one of nickel nitrate and nickel acetate; (5) The titanium source includes at least one of titanium dioxide and titanium nitrate; (6) The zirconium source includes at least one of zirconium oxide and zirconium nitrate; (7) The zinc source includes at least one of zinc acetate and zinc nitrate; (8) The metal M source is at least one of acetate, nitrate and oxide of metal M; (9) The complexing agent includes citric acid.

14. The method for preparing a positive electrode active material according to claim 12, characterized in that: The heating temperature of the heating treatment is 60° C. to 110° C.; and / or the drying temperature of the drying treatment is 80° C. to 130° C., and the drying time of the drying treatment is 5 h to 15 h.

15. The method for preparing a positive electrode active material according to any one of claims 12 to 14, characterized in that: The method further comprises a calcination step after the heat treatment, wherein the calcination step comprises the following steps: The mixed gel after drying was heated to 500°C~600°C at a heating rate of 3°C / min~8°C / min and then calcined for 3 h~7 h; The mixed gel after calcination is heated to 850°C to 950°C at a heating rate of 3°C / min to 8°C / min and then kept at this temperature for 10 h to 15 h to obtain the positive electrode active material.

16. A positive electrode slurry, characterized in that: The invention comprises the positive electrode active material as claimed in any one of claims 1 to 11 and the positive electrode active material prepared by the preparation method as claimed in any one of claims 12 to 15.

17. The positive electrode slurry according to claim 16, characterized in that The positive electrode slurry includes the positive electrode material, a conductive agent, a binder and a solvent.

18. The positive electrode slurry according to claim 17, characterized in that At least one of the following conditions is met: (1) The mass ratio of the positive electrode material, the conductive agent and the binder is 0.8-0.9: 0.03-0.2: 0.03-0.2; (2) The conductive agent includes at least one of Super P, graphene, carbon dots, CNT and Ketjen black; (3) The binder includes at least one of difluoroethylene, polyvinylidene fluoride and tetrafluoroethylene-hexafluoropropylene copolymer; (4) The solid content of the positive electrode slurry is 50% to 60%.

19. A conductive coating, characterized in that: The components of the conductive coating include the positive electrode active material, conductive agent and binder as described in any one of claims 1 to 11; or, the conductive coating is made of the positive electrode slurry as described in any one of claims 16 to 18.

20. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active layer, wherein the positive electrode active layer is arranged on at least one side of the positive electrode current collector, and the positive electrode active layer comprises the positive electrode active material according to any one of claims 1 to 11; or the positive electrode active layer is made of the positive electrode slurry according to any one of claims 16 to 18.

21. A positive electrode sheet as claimed in claim 20, characterized in that: At least one of the following conditions is met: (1) The thickness of the positive electrode plate is 0.2 mm to 0.3 mm; (2) The compaction density of the positive electrode sheet is 1.5 g / cm 3 ~3.0g / cm 3 .

22. A sodium ion battery, characterized in that: Comprising the positive electrode sheet as described in any one of claims 20 to 21.

23. An electrical device, characterized in that: Comprising the sodium ion battery as claimed in claim 22.

Citation Information

Patent Citations

  • Positive electrode active material and preparation method thereof, battery and electric device

    CN115566182A

  • Positive electrode material, preparation method thereof and sodium ion battery

    CN115966686A

  • Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

    CN116504953A

  • Layered oxide positive electrode material of sodium-ion battery as well as preparation method and application of layered oxide positive electrode material

    CN119133408A

  • Lithium ion secondary battery

    JP2019096561A

Cited By

  • Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

    CN121282158A